Training needs of reference librarians - Belem, Moctar; Wan Mamat, Wan Ali; Abu Bakar, Ahmad Bakeri (IIUM Press, 2011)
Likewise other professions nowadays, librarians must continuously equip themselves with recent and advance knowledge that focus in the library aspects. The importance of training program cannot be ignored as this program able to provide sufficient information for librarians in keeping pace with technologies and information science.